Development of starch-grafted-copolymerization with E-Caprolactone - Noradiba Abd Kadir (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
There are different types of polymers produced from feedstock derived from petrochemical or biological resources that may be demonstrated to be biodegradable. Starch, a natural biopolymer, is one of the potential materials for future biodegradable polymer products. Cassava starch and corn starch graft copolymerization with caprolactone was studied. Corn starch shows the higher percentage of grafting ratio and percentage of grafting efficiency compared to cassava starch. By using SEM, the surface morphology of starch grafted with Caprolactone in AMIMCl shows the clear connections and smooth surfaces. The Thermal Gravimetric Analysis (TGA) of the sample showed maximum decomposition temperature for cassava starch grafted PCL and corn starch grafted PCL were at 297 0C and 288 0C, respectively. Differential Scanning Calorimetry (DSC) shows that cassava starch grafted PCL showed a peak temperature at 140 C and for corn starch grafted PCL, peak temperature occurred at 130 C. The starch graft copolymerization with caprolactone had been successfully developed and can be applied for bioplastic industry.